Indeks Keandalan Gardu Induk Garuda Sakti Berdasarkan Basic Value Expected Energy Not Supplied - Henricson Sitorus; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
One of the significant purposes of reliability system analyzing is to evaluate the system’s ability to complete the load system requirement. The real problems of assessing the adequacy of the generation and bulk power transmission system about providing a dependable and suitable supply at the terminal stations can be designated as composite system reliability evaluation. The electric power system of Pekanbaru is an isolated system consisting of 4 generations, 12 substations, and 22 transmission lines. The calculated reliability evaluation by using expected energy not supplied indices at each substation in the contingency N-1. The outage of the generation unit significantly affects the EENS value in the hybrid system, the amount of capacity that comes out of the system greatly affects the value of the load that can be served. There is no EENS value when the contingency N-1 of the transmission line is due to the ring system model and the radial system as well as the large current-carrying capacity of the transmission line, so that when a contingency N-1 occurs the transmission line system can still serve all load points. The results of this study show that the EENS value existed at the release of the PLTU tenayan 1 and PLTU Tenayan 2. The EENS value is 2347,5415 MWh/ year or 0.054% of the total energy consumption in 2019 at the Garuda Sakti substation.Keywords: composite reliability, contingency, load curtailment, EENS, ETAP 12.6.